Implications of working capital management and operational continuity on company profitability in the technology sector idxtechno 2022 - Geralyn, Tirza Angel; Simbolon, Richard Friendly (Universitas Wiralodra, 2023)
Profitability is a metric to gauge a company's ability to generate satisfactory returns on its invested assets, sales, and equity. This research seeks to explore how the management of working capital and the sustained operation of companies impact their profitability within the IDXTECHNO sector over three years, from 2020 to 2022. Operating capital management is defined by three key indicators: the cash turnover ratio (CTR), inventory turnover ratio (ITR), and accounts receivable turnover ratio (ARTR). Operational continuity is assessed through the cash conversion cycle (CCC), and profitability, in this study, is represented by return on assets (ROA). A purposive sampling method was used to select seventeen sample companies, and multiple linear regression analysis was employed. The results indicate a significant influence of working capital management and operational continuity on profitability.